Ultimate Functional Preservation With Intersphincteric Resection for Rectal Cancer - Collard, Maxime; Lefevre, Jérémie H. (Frontiers in Oncology, 2020)
The proximity of the very low rectum rectal cancer to the anal sphincter raises a specific problem: how and until when can we preserve the anal continence without compromising the oncological result of the tumor resection? In this situation, intersphincteric resection (ISR) offers an excellent alternative to abdominoperineal resection (APR), but the selection of patients for this option must be extremely precise. This complex choice justifies the simultaneous consideration of an oncological approach with a functional approach in order to provide a full benefit to the patient. When a circumferential resection margin of at least 1 mm can be performed with a distal resection margin of at least 1 cm with or without preoperative radiotherapy, ISR ensures a safety choice. The oncological results of ISR reported in the literature when performed properly found a 5-year disease-free survival of 80.2% with a local recurrence rate of only 5.8%. In parallel to this oncological evaluation, the expected post-operative functional outcome and the resulting quality of life must be properly assessed pre-operatively, since partial or total resection of the internal sphincter impacts significantly on the functional outcome. Based on data from the literature, this work reports the essential anatomical considerations and then the oncological and functional elements indispensables when an anal continence preservation is evoked for a tumor of the very low rectum. Finally, the precise selection criteria and the major surgical principles are outlined in order to guarantee the safety of this modern choice for the patient.